THE RELATIONSHIP BETWEEN STIGMA AND JOB AND MARRIED ACCESSIBILITY IN HIV- AIDS PATIENTS IN KENDARI CITY: HIV- AIDS PATIENTS - Sri Zul Atmi; Tasnim Tasnim; Azis Harun (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2021)
Background:Cumulatively, HIV AIDS cases in Southeast Sulawesi Province totaled 401 cases consisting of 80 cases in Kendari City, 20 cases in Konawe, 1 case in North Konawe, 11 cases in East Kolaka, 34 cases in Kolaka, 10 cases in North Kolaka, 39 cases in South Konawe, Bombana 10 cases, Muna 27 cases, West Muna 15 cases, North Buton 26 cases, Bau-Bau 56 cases, South Buton 22 cases, Central Buton 16 cases, Buton 9 cases, Wakatobi 23 cases, and Konawe Islands District 2 cases. Meanwhile, a report from the Kendari City Health Office explained that there were an increase in HIV / AIDS positive cases in Kendari City, namely from 57 cases in 2019 an increase of 23 cases in 2020 so that the total number of HIV / AIDS cases in Kendari City was 80 cases. Methods:This research is an analytical survey research method using a cross-sectional approach. The population is all HIV / AIDS sufferers in Kendari City in 2020, amounting to 80 people. The number of samples was 67 with the sampling technique using simple random sampling. Result:Job accessibility to stigma in people with HIV / AIDS based on the chi square test analysis with a significance level of 95%, obtained the value of X2 hit = 8,242> X2 tab = 3,841; pvalue = 0.004 <value ? = 0.05, so Ho is rejected. Meanwhile, with a significance level of 95%, the value of X2 hit = 21.102> X2 tab = 3,841; pvalue = 0.000 <value ? = 0.05, so Ho is rejected for the accessibility of being married to the stigma of HIV / AIDS sufferers in Kendari City. Conclusion:There is a weak relationship between job accessibility and marriage and the stigma of HIV / AIDS sufferers in Kendari City.